Frequency, associated variables, and outcomes of acute myocardial injury according to the fourth Universal Definition of Myocardial Infarction in patients with acute ischemic stroke. (December 2022) - Stengl, Helena; Ganeshan, Ramanan; Hellwig, Simon; Klammer, Markus G; von Rennenberg, Regina; Böhme, Sophie; Audebert, Heinrich J; Nolte, Christian H; Endres, Matthias; Scheitz, Jan F
Background: Myocardial injury as indicated by elevation of cardiac troponin levels is common after acute ischemic stroke (AIS) and linked to poor outcomes. Previous studies rarely reported on serial hs-cTn measurements to distinguish whether myocardial injury is acute or chronic. Thus, little is known about frequency, associated variables, and outcome of acute myocardial injury in AIS. Methods and patients: In this single-centered observational cohort study, from 01/2019 to 12/2020, consecutive patients with neuroimaging-confirmed AIS <48 h after symptom onset, and serial troponin measurements within the first 2 days after admission (Roche Elecsys ®, hs-cardiac troponin T) were prospectively registered. Acute myocardial injury was defined according to the fourth Universal Definition of Myocardial Infarction (troponin above the upper reference limit and rise/fall>20%). Outcomes of interest were in-hospital mortality and unfavorable functional status at discharge (modified Rankin Scale >1). Results: Out of 1067 analyzed patients, 25.3% had acute myocardial injury, 40.4% had chronic myocardial injury and 34.3% had no myocardial injury. Older age, higher stroke severity, thrombolytic treatment, and impaired kidney function were independently associated with acute myocardial injury. In-hospital mortality was higher in patients with acute myocardial injury than in those without (13% vs 3%, adjusted OR, 2.9% [95% CI, 1.6–5.5]). Compared with no myocardial injury, both acute and chronic myocardial injury were associated with unfavorable functional status at discharge (adjusted OR, 1.6 [95% CI, 1.1–2.5] and OR, 1.7 [95% CI, 1.2–2.4], respectively). Conclusions: A quarter of patients with AIS have evidence of acute myocardial injury according to the fourth Universal Definition of Myocardial Infarction. The strong association with in-hospital mortality highlights the need for clinical awareness and future studies on underlying mechanisms.